The shaping of plant axes and crowns through tropisms and elasticity an example of morphogenetic plasticity beyond the shoot apical meristem - Moulia, Bruno (The New phytologist, 2022)
© 2021 The Authors. New Phytologist © 2021 New Phytologist Foundation.